Prevalence of Diagnosed Sleep Disorders and Related Diagnostic and Surgical Procedures in Children with Autism Spectrum Disorders. Issue 5 (June 2016) - Elrod, Marilisa G.; Nylund, Cade M.; Susi, Apryl L.; Gorman, Gregory H.; Hisle-Gorman, Elizabeth; Rogers, Derek J.; Erdie-Lalena, Christine
ABSTRACT: Objective: Sleep disorders are common and important comorbid conditions in children with autism spectrum disorder (ASD) and can contribute to cognitive and behavioral problems. Sleep-disordered breathing (SDB) is a diagnosable and treatable cause of behavioral problems in children. We aimed to quantify the relative risk for children with ASD versus controls of being diagnosed with sleep disorders including SDB and undergoing related diagnostic and surgical procedures. Method: This retrospective case-cohort study included 48, 762 children with ASD aged 2 to 18 years enrolled in the military health system (MHS) from 2000 to 2013. Children with ASD were matched 1:5 by birthdate, sex, and enrollment time to children without an ASD diagnosis. The MHS database was queried for International Classification of Diseases, Ninth Revision, Clinical Modification ( ICD-9-CM ) codes for sleep disorders or ICD-9-CM and Current Procedural Terminology codes for diagnostic and surgical procedures. Relative risks (RR) and 95% confidence intervals (CI) were determined with binary Poisson regression conditional on the match and adjusting for confounders. Results: Children with ASD were at higher risk of receiving any sleep disorder diagnosis (RR: 1.97 [95% CI, 1.91–2.02]) including SDB (RR: 1.96 [95% CI, 1.88–2.05]). Children with ASD also were at increased risk of undergoing polysomnography (RR: 3.74 [95% CI, 3.56–3.93]) and sleep disorder-related surgery (RR: 1.50 [95% CI, 1.46–1.54]). Conclusion: Children with ASD are more likely to be given a sleep disorder diagnosis including SDB and are more likely to undergo related diagnostic and surgical procedures compared with controls without ASD. Abstract : This article has supplementary material on the web site: www.jdbp.org.